Layanan BK Islam Guna Mencegah Kekerasan Seksual Di Kalangan Siswa SMA Muhammadiyah Sambas - Manja; Kartika (Jurnal Ilmiah Al-Muttaqin, 2025)
This research aims to find out, namely 1) The objectives of Islamic BK services to prevent sexual violence among students; 2) The principles of Islamic BK services to prevent sexual violence among students; 3) The implementation of Islamic BK services to prevent sexual violence among students. This study uses a qualitative approach and employs a descriptive type. Mr. Ilham Ansori, S.Pd., a guidance and counseling teacher who offers Islamic counseling to prevent sexual violence among students, is the data source for this research. Data were collected through observation, interviews, and documentation. For now, data analysis uses an interactive data analysis approach, and methods to verify data validity using triangulation and member check. The results of this study show that the Islamic BK services aimed at preventing sexual violence among students at SMA Muhammadiah Sambas include: 1) The goal of the Islamic BK services to prevent sexual violence among students is to help students make decisions and create plans to implement those decisions, so that they behave or take actions that are constructive in accordance with Islamic teachings. 2) The principles of Islamic BK services to prevent sexual violence among students are based on the following principles: a) happiness in this world and the hereafter; b) selflessness (for the sake of Allah); c) lifelong guidance; d) the development of noble character; and e) consultation. 3) The implementation of Islamic BK services to prevent sexual violence among students is carried out in three forms of services, namely: a) information; b) learning; c) group guidance.